The fama and french six-factor model : evidence for the german market - Novak, Daniel Georg (2022)
The Fama and French models have influenced the research around multi-factor asset pricing in the past decades as no other approach (Fama and French 1993; 2015; 2018). In search of patterns and bias that tend to explain stock performances, investors and financial theorists continuously investigate the three-, five-, and recent six-factor models and their individual factors in different markets. In their well-known papers, Fama and French developed the models over various years based on data for the US market starting in July 1963. Almost simultaneously with the enhancement evolved also more research regarding the models’ applicability and robustness in other markets outside the US. However, even though insights about the international evidence of the models increased, significant research on the German market is still rare. The present work analyzes the explanatory power of the Fama and French Six-Factor Model (FF6) on average stock returns in Germany. Data is collected from Thomson Reuters Datastream and Worldscope for the time between July 1982 and June 2021 and I create factor portfolios according to the criteria defined by Fama and French. The evaluation shows a tendency for superior performance of the Fama and French Six-Factor Model over the previous three- and five-factor models. While big stocks seem to perform better than small stocks, there is indication for value and momentum premiums in the German market. Nevertheless, the results reveal only weak evidence for the explanatory power of the Fama and French Six-Factor Model on average stock returns in Germany.